Asessment of elite Indian wheat genotypes for drought tolerance - Divya Ambati, Rahul M Phuke*, JB Singh, SV Sai Prasad and Sanjay Parihar (Electronic Journal of Plant Breeding)
To understand the plasticity of adaptation to different environmental conditions, eighteen elite wheat genotypes were evaluated for two seasons (2017-18 and 2018-19) under water-stress and controlled environments at ICAR-Indian Agricultural Research Institute (IARI), Regional station, Indore, India. Combined analysis of variance for grain yield under both water regimes showed that effects due to the water regimes, environment and genotype all interactions were found to be significant. Genotypes viz., NI 5439, HI 8791and HI 1531 were found to perform stable under both water regimes with high mean yield. Based on PCA biplot and GGE biplot analysis it is evident that genotypes HI 8793, HI 8790 and HI 1619 were the highly adapted, most stable and high yielding genotypes. HI 8791, HI 1531, NI 5439, HI 8793, HI 8790 and HI 1619 were identified to be stable for grain yield and can be utilized further in the breeding program for climate resilient wheat varieties development.